2016
DOI: 10.14347/kadt.2016.38.3.247
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Relationship Between Job Seeking Stress and career decision-making self-efficacy in students of Department of Dental Technology

Abstract: Purpose: This study is to analyse the job seeking stress, to see the relationship Between Job Seeking Stress and career decision-making self-efficacy in students of department of dental technology.Method: For this, the students of department of dental technology in daegu and daejeon and wonkwang university selected at May 2016. A question investigation was used in a entry method of self-estimation. Furthermore a total of 151 person was used as final analysis data. Statical analysis was performed with SPSS 22.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…We found no significant association between gender and CDMS. e findings of some studies were similar [29,40], but some studies showed a significant relationship between gender and CDMS [41,42]. erefore, the findings were controversial.…”
Section: Discussionmentioning
confidence: 76%
“…We found no significant association between gender and CDMS. e findings of some studies were similar [29,40], but some studies showed a significant relationship between gender and CDMS [41,42]. erefore, the findings were controversial.…”
Section: Discussionmentioning
confidence: 76%